Investigation of the parameters affecting the thermosiphonic phenomenon in solar water heaters - Kalogirou, Soteris A.; Panayiotou, Gregoris; Florides, Georgios A.; Roditis, George; Katsellis, N.; Constantinou, A.; Kyriakou, P.; Vasiades, Y.; Parisis, Thomas; Michaelides, Alexandros; Nielsen, Jan Erik (My University, 2013)
Cyprus is currently the leading country in the world with respect to the application of solar water heaters for domestic applications, with more than 93% of the houses equipped with such a system. The great majority of these solar water heaters are of the thermosiphonic type. Thermosiphonic is a natural phenomenon where the flow of the solar heated water from the collector to the storage tank occurs from a small flow created due to the difference in density between hot and cold water. The main advantage of such systems is that they do not require a pump for circulating the water and circulation exists as long as there is sunshine. This reduces the maintenance requirements and the system is foolproof. In spite of the fact that extensive analyses of the performance of solar water heaters has been carried out by numerous researchers, almost all of them concerned forced circulation systems which use a circulating pump. Currently, the knowledge on the parameters affecting the ‘thermosiphonic phenomenon’ is rather poor while on an international level (ISO and CEN committees) there isn’t any standard to test thermosiphon solar collectors. The deeper understanding of the ‘thermosiphonic phenomenon’ and the identification of the key parameters affecting it, is the main aim of a research project currently in process in Cyprus. In this work the first preliminary results of the experimental procedure are presented. More specifically, a special test rig was set up and equipped with all sensors necessary to measure all parameters that are most likely to affect the ‘thermosiphonic phenomenon’. All tests were conducted according to ISO 9459- 2:1995(E). The system was able to operate in various weather and operating conditions and could accommodate the change of inclination of the collector. Initially, the solar collector was tested according to EN12975-2:2006 in order to determine the thermal performance at a flow and operation conditions specified by the standard. Subsequently, the efficiency of the collector operating thermosiphonically was calculated based on quasi-dynamic approach. Finally, a series of correlations were attempted using the data acquired when the collector is operating themosiphonically which are the following: (i) the temperature difference of the water at the outlet and the inlet of the collector (ΔΤ) with the solar global radiation, (ii) the water mass flow with the solar global radiation, (iii) the water mass flow with the temperature difference of the water at the outlet and the inlet of the collector (ΔΤ). The results of the data analysis showed that these parameters are very well correlated between them since the coefficient of determination (R2) is over 0.91 in all cases.
Keywords: Thermosiphonic phenomenon; Solar water heaters; Cyprus